Penerapan Metode Tanya Jawab Pada Mata IPS Untuk Meningkatkan Hasil Belajar Siswa Kelas V SD Negeri 206 Apala Kabupaten Bone - rosdiana rosdiana; Nursiah Nursiah (Universitas Negeri Makassar, 2019)
The problem in this study is to find a picture of increasing student learning outcomes through the question and answer method in social science subjects (IPS) in class V SD Negeri 206 Apala Bone Regency. This research is a descriptive study with the focus of the research is 10th grade students of Elementary School 206 Apala Bone Regency. Collecting data with observation techniques, tests, and documentation, while Collecting data with observation techniques to capture data analysis activity data used is descriptive statistical analysis in the form of percentages and frequency tables. The results obtained by Grade V students of Elementary School 206 Apala Bone Regency in general experienced an increase in learning outcomes in social studies through question and answer by paying attention to aspects, namely: (a) increasing social studies learning outcomes, (b) being able to conduct question and answer to teachers or students another. While the efforts taken by teachers in the field of Social Sciences (IPS) studies in improving the learning outcomes of class V students, namely (a) training students to dare to ask questions, (b) training students to answer.